2018
DOI: 10.1088/1361-6463/aaa926
|View full text |Cite
|
Sign up to set email alerts
|

Sandwich method to grow high quality AlN by MOCVD

Abstract: We report pulsed atomic layer epitaxy growth of a very high crystalline quality, thick (~2 µm) and crack-free AlN material on c-plane sapphire substrates via a sandwich method using metal organic chemical vapor deposition. This sandwich method involves the introduction of a relatively low temperature (1050 °C) 1500 nm thick AlN layer between two 250 nm thick AlN layers which are grown at higher temperature (1170 °C). The surface morphology and crystalline quality remarkably improve using this sandwich method. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…A~20 nm thick low temperature AlN nucleation layer then 300 nm thick high temperature PALE (pulsed atomic layer epitaxy) AlN were grown on sapphire substrate. Growth details of this AlN/sapphire template were explained in detail in previous studies [8,14]. Three (A, B and C) different AlGaN epilayers were grown on optimized AlN/sapphire template at 1020, 1180 and 1220 C, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…A~20 nm thick low temperature AlN nucleation layer then 300 nm thick high temperature PALE (pulsed atomic layer epitaxy) AlN were grown on sapphire substrate. Growth details of this AlN/sapphire template were explained in detail in previous studies [8,14]. Three (A, B and C) different AlGaN epilayers were grown on optimized AlN/sapphire template at 1020, 1180 and 1220 C, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…substrates, [28][29][30] and manipulating the growth mode via temperature or V-III ratio. [31][32][33][34] Imura et al have reported the varying V-III ratio multilayer transition growth method to improve AlN crystalline quality, which gradually changed from high ammonia (NH 3 ) flow rate at buffer layer to low flow rate at top layer. [31] They have confirmed that regulating the V-III ratio could promote the dislocation annihilation.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, AlN-based devices are generally grown on silicon and sapphire substrates. The heteroepitaxial growth of the high crystal quality AlN epitaxial layer on different substrates is one of the most important problems in the literature [15]. AlN layer can be grown more difficult for reasons such as growth at higher temperatures (~ 1200 °C) compared to GaN [16], the high parasitic reaction between TMAl (Al(CH3)3) and NH3 [17], and the low surface mobility of the Al atom [18].…”
Section: Introductionmentioning
confidence: 99%